The CCR5 delta 32 polymorphism (rs333) is not associated with Sjögren's syndrome or Type 1 Diabetes in Colombians (2013)
Sjögren's syndrome (SS) and Type 1 Diabetes (T1D) are chronic, progressive autoimmune diseases that affect exocrine glands or ?-cells in the islets of Langerhans in the pancreas, respectively. Typical features of both diseases include production of antibodies against self-antigens and T and B cell infiltrates in organ-specific tissues [12] . Migration of pro-inflammatory memory T cells and monocytes into chronically inflamed tissues is driven by Th1-related chemokines and their receptors. This includes CCR5, a seven-transmembrane domain G protein-coupled receptor (GPCR) involved in intracellular signaling [3] . In Sjögren's syndrome, mRNA and receptor expression of CCR5 are significantly upregulated in inflammatory Th1 cells, parotid gland excretory ducts and conjunctival epithelium of SS-affected individuals indicating that it has a significant role in the progression and severity of pSS disease [45] . In Type 1 Diabetes, recruitment of activated CCR5-expressing T cells to the pancreas or kidney can promote renal disease and impairment of insulin production [6] .